Om jalousitemaet hos Proust - Buvik, Per (Passage - Tidsskrift for litteratur og kritik, 2015)
Per Buvik: “On the Theme of Jealousy in Proust” In Proust, there is generally no love without jealousy. More surprisingly, jealousy is even prior to love, which is, then, derived from jealousy. Love is consequently dominated by uncertainty, suspiciousness, and anguish, represented as rooted in early childhood. Suffering from a never surmounted Oedipus complex, Proust’s narrator and main character constantly compares his girlfriend Albertine with his mother when he was a child, longing for the same intimacy, but also fearing the same “treachery” that he experienced with her. Only long-lasting separation or boredom due to long-lasting daily life together can eliminate jealousy. The problem is that love also disappears when there is no jealousy.